2001
DOI: 10.1097/00129492-200105000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Skull Base Surgery for Glomus Tumors: Long-Term Control

Abstract: Surgical resection of glomus tumors is established as an effective technique with good functional outcomes and long-term control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
144
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(156 citation statements)
references
References 11 publications
4
144
1
2
Order By: Relevance
“…This is consistent with the rates of deficits reported in other series. In the one reported by Jackson et al, 16 new deficits were found in CNs IX, X, XI, and XII in 39%, 25%, 26%, and 21% of cases, respectively.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This is consistent with the rates of deficits reported in other series. In the one reported by Jackson et al, 16 new deficits were found in CNs IX, X, XI, and XII in 39%, 25%, 26%, and 21% of cases, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…25 Surgical approaches are challenging because of the proximity of critical vascular and neural structures that are frequently invaded by the tumor. 1,18 Jackson and colleagues 16 reviewed 18 cases of incompletely resected tumors and found that 9 of them had progressed to the point that they required further interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 With the advent of improved microsurgical techniques and the use of combined approaches, the mortality rate has lowered substantially; however, cranial nerve injury continues to be a problem. [18][19][20][21] In a retrospective series of 176 patients treated between 1972 and 1998 and reported by Jackson, et al, 12 in 85% complete surgical control was described. The remaining 15% of their patients had a subtotal resection or recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…44 In 1987, Al-Mefty et al 1 described a combined approach for giant glomus tumors with intracranial extension, previously believed to be inoperable, again expanding the spectrum of tumors amenable to resection. The ability to achieve effective gross-total resection in the microsurgical era was illustrated in 2001 26 in one of the largest series of glomus tumors to date. In this publication, Jackson et al 26 reported on the surgical results following 182 procedures for resection of glomus tumors involving the skull base; 152 of the procedures involved jugulotympanic glomus tumors.…”
Section: Evolution In Tumor Managementmentioning
confidence: 99%